Development of Creativity and LinguisticMethodical Thinking of Students of Pedagogical University - A. Shakirova, Alina; F.Yusupova, Zulfiya; V. Gordienko, Oksana; Kadyrkulova UpelК. (International Journal of Psychosocial Rehabilitation, 2024)
This article presents the research materials on the modern and urgent problem of the formation of linguistic and methodological thinking of students of pedagogical high school in the conditions of implementation of creative approaches in the classroom and in independent educational activities. Creativity, considered the ability to engage in creative activity, is a necessary condition for the development of the creative potential of the student. In the traditional sense, the most important indicators of creativity are such qualities as the ability to detect a problem, generate original ideas, etc. the Creation of situations in the educational process that require students to make independent creative decisions contributes to the development of creativity as a quality of personality. In this regard, in the educational process introduced methods of formation of creativity, such as problem solving, stimulating the installation of self-discovery of new knowledge. The lack of theoretical information on the development of linguistic and methodological thinking of students and the imperfection of the methodological system of its development in the pedagogical University lead to fragmentary knowledge, which entails a lack of skills in mastering the disciplines of the methodical cycle of students, which leads to difficulties in solving professional problems. Modern linguistic and methodological preparation of students of pedagogical universities is intended to increase cognitive and creative orientation to learning; therefore, the study was created and implemented in the educational process theoretically grounded experimental methods of training of students of pedagogical universities. The results of the experimental training showed that the creative component stimulates the thinking of students, motivates them to self-acquisition of knowledge, to their creative use in the solution of problematic professional (methodical) tasks, and promotes the full assimilation of knowledge and the development of linguistic thinking.